Respuesta :
Answer:
y=-2
Step-by-step explanation:
9(y−4)−7y=5(3y−2)
(9)(y)+(9)(−4)+−7y=(5)(3y)+(5)(−2)
9y+−36+−7y=15y+−10
(9y+−7y)+(−36)=15y−10
2y+−36=15y−10
2y−36=15y−10
Step 2:
2y−36−15y=15y−10−15y
−13y−36=−10
Step 3:
−13y−36+36=−10+36
−13y=26
divide
/13 /13
y=-2
Answer:
y=-2
Step-by-step explanation:
Simplifying
9(y + -4) + -7y = 5(3y + -2)
Reorder the terms:
9(-4 + y) + -7y = 5(3y + -2)
(-4 * 9 + y * 9) + -7y = 5(3y + -2)
(-36 + 9y) + -7y = 5(3y + -2)
Combine like terms: 9y + -7y = 2y
-36 + 2y = 5(3y + -2)
Reorder the terms:
-36 + 2y = 5(-2 + 3y)
-36 + 2y = (-2 * 5 + 3y * 5)
-36 + 2y = (-10 + 15y)
Solving
-36 + 2y = -10 + 15y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-15y' to each side of the equation.
-36 + 2y + -15y = -10 + 15y + -15y
Combine like terms: 2y + -15y = -13y
-36 + -13y = -10 + 15y + -15y
Combine like terms: 15y + -15y = 0
-36 + -13y = -10 + 0
-36 + -13y = -10
Add '36' to each side of the equation.
-36 + 36 + -13y = -10 + 36
Combine like terms: -36 + 36 = 0
0 + -13y = -10 + 36
-13y = -10 + 36
Combine like terms: -10 + 36 = 26
-13y = 26
Divide each side by '-13'.
y = -2
Simplifying
y = -2